The Effectiveness of Online Advertising on Consumers’ Mind – An Empirical Study - Rashid Farooqi, Md; Faiz Ahmad, Md (International Journal of Engineering and Technology, 2018)
This paper helps to investigate the effectiveness of online advertisement on consumers' mind. The data, which has been obtained from the respondents of Hyderabad, showed an impact on the consumers’ perception about the online advertising. A survey was conducted through structured questionnaire to obtain the data from the respondents of University of Hyderabad (UoH) and Maulana Azad National Urdu University (MANUU) situated in Hyderabad. A sample of 200 respondents were gathered with in a time frame of one month and their responses were analyzed with the help of Statistical Package for Social Science (SPSS) by using different statistical techniques in order to know the effectiveness of online advertisement on consumer mind. The outcome shows a positive impact of advertising on consumer’s mind.